2012
DOI: 10.1021/jf3001923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sampling Size on the Determination of Accurate Pesticide Residue Levels in Japanese Agricultural Commodities

Abstract: The uncertainty in pesticide residue levels (UPRL) associated with sampling size was estimated using individual acetamiprid and cypermethrin residue data from preharvested apple, broccoli, cabbage, grape, and sweet pepper samples. The relative standard deviation from the mean of each sampling size (n = 2 x , where x = 1–6) of randomly selected samples was defined as the UPRL for each sampling size. The estimated UPRLs, which were calculated on the basis of the regulatory sampling size recommended by the OECD G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The median residues in cabbage were 0.116 and 0.056 mg/kg for acetamiprid and cypermethrin, respectively, which were lower than their mean values described above. The skewed distribution of pesticide residues in cabbage was not observed for the other raw agricultural commodities, such as apples, broccolis, and sweet peppers. , The median residues in grapes were 1.33 and 1.86 mg/kg for acetamiprid and cypermethrin, respectively, which were the same as their mean values.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The median residues in cabbage were 0.116 and 0.056 mg/kg for acetamiprid and cypermethrin, respectively, which were lower than their mean values described above. The skewed distribution of pesticide residues in cabbage was not observed for the other raw agricultural commodities, such as apples, broccolis, and sweet peppers. , The median residues in grapes were 1.33 and 1.86 mg/kg for acetamiprid and cypermethrin, respectively, which were the same as their mean values.…”
Section: Resultsmentioning
confidence: 55%
“…The measured VFs of the above tested commodities ranged from 1.48 for cypermethrin in sweet peppers to 1.76 for cypermethrin in apples. These studies provided a valuable piece of information to estimate the variations in pesticide residues under normal Japanese agricultural practices . However, these results are not sufficient to clarify the influence of complex factors such as differences in crop species, plant cultivation methods, and physicochemical properties of the pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, studies involving pesticide application field trials have shown current practices to be acceptably precise (<25% RSD) if carried out according to common regulatory standards (e.g., EPA, OECD, FAO/WHO, Codex). Similarly, sampling studies for regulatory monitoring have shown similarly good precision if enough replicate samples (≥6 from 8–12 lots) are taken, but this has been shown to depend significantly on analyte/commodity pairs. Ambrus has recommended collecting 10–25 increments per sample, which has been shown to yield 16–25% uncertainty . For a typical field trial of fruit trees, this translates into collecting samples from at least half of the trees dispersed randomly within a given plot and compositing 24 fruits per sample .…”
Section: Current Sampling Practicesmentioning
confidence: 99%
“…There are a great variety of factors that are responsible for this variation of residues such as type of pesticide formulation, method of pesticides application, type of sprayers used, mode of cultivation, height and shape of plants, soil characteristics and soil dissipation factors, weather conditions, etc. Up until now, a number of field experiments have been conducted to estimate the residue variability in/on small (the individual unit weight < 25 g) and medium size (individual unit weight > 25–250 g) fruit crops, 4‐15 while only a few field experiments have been conducted so far on large size (individual unit weight > 250 g) fruit crops 6,12 . Therefore, the estimation of VFs with the marketed samples of large, medium and small size fruit crops are very limited 9,16‐20 …”
Section: Introductionmentioning
confidence: 99%